61‐3: Invited Paper: Research on Switchable Privacy Mode Applied to Automotive Displays. Issue 1 (28th June 2022) - Zhang, Zhipeng; Zhai, Yue; Dong, Xiaoqiao; Cai, Site; Yoon, DK; Ma, Qing; Han, Rui; Yu, Jie; Cui, Dong; Zhu, Yuanyuan
Abstract : The concept of switchable privacy display has been successfully applied to notebooks and other consumer display products [1]. However, when applied to automobile display modules, their unique application scenarios, such as display to the co‐driver's side or CID, should also be considered (see Figure 1‐1 for viewing angle requirements). And BOE has developed display modules for application in automotive displays.